JARINGAN SOSIAL MIGRAN BURUH TANI PADA MASA SULIT (STUDI KASUS KELURAHAN GUNDALING I KECAMATAN BERASTAGI KABUPATEN KARO) - Siahaan , Angelina. R; Ginting, Bengkel (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2022)
This study aims to describe the social network owned by migrant farm workers in Kelurahan Gundaling I Kecamatan Berastagi Kabupaten Karo in facing difficult times. This research method is descriptive qualitative with life story case studies. The main informants in this study were three migrant farm workers who had worked as farm laborers and resided in Gundaling I Village, Berastagi District, Karo Regency for at least 5 years and had a family, the key informant in this study was the head of the Gundaling I Village and additional informants were elders in Gundaling I Village. Data were collected through observation, interviews and documentation. The results of this study show how a broad social network can help in dealing with difficult times, and good social network relationships can result in a patron-client relationship.